Captain Marvel [videorecording (Blu-Ray)] - Lee, Stan, 1922-2018 (Marvel Studios, 2019)
Carol Danvers becomes one of the universe's most powerful heroes as a human imbued with abilities gifted from the Kree, where she has been training as a warrior. Returning to Earth on assignment in a war between two alien races, she finds her memories returning to her, and must decide exactly where her allegiances lie, and how -- or if -- she will embrace her full power.